Knowledge, Attitude and Practice of Mothers Regarding Weaning and Occurrences of Iron Deficiency Anaemia in Children 6-60 Months - Sofia Nawaz, Najma Parveen, Sidra Farooq, Sundas Jaafar, Kinza Jafar, Hamza Nawaz (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the awareness and practices of mothers of infant’s age 6 to 60 months regarding weaning and its association with anaemia. Study Design: Cross-sectional study. Place and Duration of Study: Department of Paediatric Medicine, Shaikh Zayed Hospital Lahore from 1st November 2021 to 30th April 2022. Methodology: Four hundred forty mothers were enrolled. A self-designed questionnaire was used to collect data concerning knowledge attitude and practices of mothers of children between ages 6-60 months. Results: There is an association which is statistically significant of anaemia history of children with multiple factors like infant gender (p=0.008), child age (p=0.005), age of weaning start (p=0.051), infant feeding habit (p=0.022), dietary diversity relation (p=0.001), infant caregivers (p-=0.043), child history of Pica (p=0.013), food type and frequency intake (p=0.003) (both healthy and unhealthy foods). While, there was no significant association of healthy food with anaemia (p=0.077). Conclusion: Mothers had sufficient knowledge regarding weaning practices of infants. However late start of weaning infant feeding habits were contributory factors of iron deficiency anaemia among children. Keywords: Weaning, Iron deficiency anaemia, Mothers knowledge, Children under 5 years